The Influence of Risk Aversion on Brand Loyalty with Brand Trust and Brand Affect as Mediating Variables - Wicaksono, Nurfuad (ASEAN Marketing Journal, 2023)
Currently cosmetic products are no longer only intended for women, but also for men. Thus, creating opportunities and a conducive environment for the emergence of new companies. With the increasing number of companies in the men's cosmetic industry today, how to build brand loyalty is one of the biggest challenges companies will face. This study aims to explore the relationship between risk aversion and brand loyalty, and test whether this relationship is mediated by brand trust and brand affect on the purchase of cosmetic and body care products by men. The selection of the sample was carried out using a purposive sampling method with 130 respondents whose criteria were male students at Ciputra University Surabaya. Data analysis used the SEM-PLS variant-based structural equation method with the SmartPLS 4 program. The results showed that risk aversion was statistically significant in influencing brand trust, brand affect, and brand loyalty. Brand trust and brand affect are also statistically significant in influencing brand loyalty. By analyzing brand loyalty and the variables that influence it, cosmetic and men's body care product companies can understand how to develop brand loyalty, especially by paying attention to the aspects of risk aversion, brand trust, brand affect, and brand loyalty.